Perhitungan Volume Pekerjaan Struktur Proyek Rumah Cluster Bukit Golf Menggunakan Autodesk Revit - Suharianto, Dimas Aditya (Universitas Negeri Surabaya, 2023)
The development of Indonesian construction has developed quite rapidly which is also balanced by technological developments. The development of technology is useful for construction projects to help plan the calculation of the volume of structural work, one of the software used is Autodesk Revit. The research was conducted on the Bukit Golf cluster house by calculating the volume of structural work on the foundation elements, sloofs, columns, beams, and plates which were then compared with the existing volume. The research method used for volume calculation is using Autodesk Revit software. The results of volume calculations using Autodesk Revit software obtained a total volume of concrete of 380.401 m3, while the total volume of reinforcement obtained was 48520.990 kg. The difference in the calculation of concrete volume using autodesk revit with conventional is 9.84%, while the difference in the calculation of reinforcement volume using autodesk revit with conventional is 19.61%. So that the calculation of the volume of concrete structure work and reinforcement using Autodesk Revit software is more efficient and efficient. The difference in volume calculation occurs due to the volume calculated using autodesk revit software is calculated net once at the meeting between structural elements.